Investigating the Effect of Porosity and Pore Shape on Porous Polymer Structure Under Axial Compression and Buckling Behaviour - Mohd Yusof, Ab Aziz (International Journal of Integrated Engineering, 2024)
The strength and durability of porous polymer structures under compression and bending remain a significant challenge in engineering. The pore structure needs to be designed to have proper strength and be capable of fulfilling the function. Their mechanical properties and stability under compressive loads are critical factors in determining their success. Despite extensive research on the porous structure related to polymers, the failure mechanics and the characteristics of the porous polymer structure were found to be limited. Therefore, the study was carried out to investigate the effect of the porosity and pore shape under axial compression and bending. There is a need to investigate the underlying mechanisms of porous polymers to develop accurate strategies to improve their mechanical properties and stability. The porous polymer's square and circle hole shape was fabricated using 3D printing for five structure porosities: 30%, 40%, 50%, 60%, and 70%. The study found that the porous polymer deforms up to 5% strain elastically. Higher porosity led to significant stress reduction, with a linear decrease in maximum compression force correlating with porosity, and circle pores exhibited better performance. The Pearson correlation highlighted a consistent, predictable inverse relationship between porosity and compression force. In conclusion, the study revealed the complex mechanical behaviour of a porous polymer under compression. The result offered important details, helping to understand the connections between porosity, compression force, and the structure's strength.